Metformin for women who are overweight or obese during pregnancy for improving maternal and infant outcomes - Dodd, Jodie M (Cochrane Database Syst Rev, 2018)
BACKGROUND: There has been considerable interest in providing antenatal dietary and lifestyle advice for women with obesity or who are overweight during pregnancy, as a strategy to limit gestational weight gain and improve maternal and infant health. However, such antenatal interventions appear to have a modest effect on gestational weight gain and other clinical pregnancy and birth outcomes and additional strategies are required. Metformin is an oral insulin‐sensitising medication that acts to decrease blood glucose concentrations. Metformin is commonly used in the treatment of type 2 diabetes mellitus and polycystic ovarian syndrome, and is being used increasingly in the treatment of gestational diabetes, having been shown to result in decreased rates of caesarean birth and neonatal hypoglycaemia. Metformin may be an adjuvant therapy to current antenatal strategies in pregnant women with obesity or who are overweight, acting to reduce glucose production in the liver and improve glucose uptake in smooth muscle cells, and therefore improve the overall metabolic health of women in pregnancy and reduce the risk of known adverse pregnancy outcomes. OBJECTIVES: To evaluate the role of metformin in pregnant women with obesity or who are overweight, on maternal and infant outcomes, including adverse effects of treatment and costs. SEARCH METHODS: We searched Cochrane Pregnancy and Childbirth's Trials Register, ClinicalTrials.gov, the World Health Organization (WHO) International Clinical Trials Registry Platform (ICTRP) (11 October 2017), and reference lists of retrieved studies. SELECTION CRITERIA: All published and unpublished randomised controlled trials evaluating metformin use (compared with placebo or no metformin) in women with obesity or who are overweight in pregnancy for improving outcomes, alone or in combination with other interventions were eligible for inclusion. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trials for inclusion and risk of bias, extracted data and checked them for accuracy. We used the GRADE approach to assess the quality of the evidence. MAIN RESULTS: We included three studies which randomised women (1099) with a body mass index (BMI) of 30 kg/m(2) (1 study) and 35 kg/m(2) (2 studies), with outcomes available for 1034 participants. None of the studies assessed women with a BMI between 25 kg/m(2)and 29.9 kg/m(2), therefore we could not assess the use of metformin in women considered overweight. We did not identify studies of metformin in combination with another treatment. Two other studies are ongoing. All three included studies were randomised controlled trials and compared metformin with placebo, commencing early in the second trimester. Doses ranged from 500 mg twice daily to 3.0 g per day. All three studies (two in the UK, one in Egypt) included women attending hospitals for antenatal care. Two studies were generally at a low risk of bias across the majority of domains. We assessed the third study as being at an unclear risk of selection bias, performance and detection bias due to insufficient information in the report. We assessed the trial as being at a low risk of attrition bias and other bias; we felt it was at a high risk of reporting bias. The primary outcome for this review was infant birthweight large‐for‐gestational‐age (> 90th centile for gestational age and infant sex). Women who received metformin or placebo had a similar risk of their baby being born large for his or her gestational age (risk ratio (RR) 0.95, 95% confidence interval (CI) 0.70 to 1.30; 2 studies, 831 infants; high‐quality evidence). Women who received metformin may have a slightly lower gestational weight gain (mean difference (MD) ‐2.60 kg, 95% CI ‐5.29 to 0.10; 3 studies, 899 women; low‐quality evidence). Metformin may make little or no difference in the risk of women developing gestational hypertension (average RR 1.02, 95% CI 0.54 to 1.94; 3 studies, 1040 women; low‐quality evidence) or pre‐eclampsia (RR 0.74, 95% CI 0.09 to 6.28; 2 studies, 840 women; low‐quality evidence). Metformin probably makes little or no difference in the risk of women developing gestational diabetes (RR 0.85, 95% CI 0.61 to 1.19; 3 studies, 892 women; moderate‐quality evidence). One study of 400 women reported women receiving metformin were more likely to experience any adverse effect compared with women receiving placebo (RR 1.63, 95% CI 1.27 to 2.08; 1 study, 400 women). Adverse effects included abdominal pain, diarrhoea, or headache. When considering individual side effects, women receiving metformin were more likely to experience diarrhoea than women receiving placebo (RR 2.34, 95% CI 1.74 to 3.14; 797 women; 2 studies, 797 women; high‐quality evidence). No other important differences were identified between Metformin and placebo for other maternal secondary outcomes, including: caesarean birth, birth before 37 weeks of pregnancy, shoulder dystocia, perineal tear, or postpartum haemorrhage. In terms of other infant outcomes, there was little or no difference in the infant birthweight (MD 6.39 g, 95% CI ‐81.15 to 93.92; 2 studies, 834 infants; high‐quality evidence). There were no other important differences identified for other infant secondary outcomes in this review: hypoglycaemia (low blood sugar); hyperbilirubinaemia (jaundice); Apgar score less than 7 at five minutes; or stillbirth and neonatal death. Only one study reported admission to the neonatal intensive care unit (NICU), indicating similar rates of admission between women receiving metformin or placebo; no other admission data were reported to assess differences in costs. AUTHORS' CONCLUSIONS: There is insufficient evidence to support the use of metformin for women with obesity in pregnancy for improving maternal and infant outcomes. Metformin was, however, associated with increased risk of adverse effects, particularly diarrhoea. The quality of the evidence in this review varied from high to low, with downgrading decisions based on study limitations and inconsistency. There were only a small number of studies included in this review. Furthermore, none of the included studies included women categorised as 'overweight' and no trials looked at metformin in combination with another treatment. Future research is required in order to further evaluate the role of metformin therapy in pregnant women with obesity or who are overweight, as a strategy to improve maternal and infant health, alone or as an adjuvant to dietary and lifestyle advice.